Implementasi Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Berdiferensiasi - Adinda Amalia Azzahra Lubis; Khairurrijal Khairurrijal; Anni Marhamah (An-Nuha, 2025)
This study aims to determine the implementation of content differentiation, process differentiation, and product differentiation in Islamic religious education learning at SDN 193 Kotanopan. This study employed qualitative methods, which are used to comprehensively understand an event or activity by collecting information through interviews, observation, and documentation, then explaining the results in words rather than numbers. Data analysis techniques included data reduction, data presentation, and drawing conclusions. Data validity was verified through triangulation and member checking. The results indicate that content differentiation was implemented by adapting material based on diagnostic assessment results to meet students' learning needs. Process differentiation was implemented using learning variations appropriate to students' styles, interests, and readiness. Product differentiation was implemented by teachers adapting the format of the final assignment so that students could demonstrate their understanding based on their individual abilities.